Early expansion of myeloid-derived suppressor cells inhibits SARS-CoV-2 specific T-cell response and may predict fatal COVID-19 outcome - Sacchi, Alessandra; Grassi, Germana; Bordoni, Veronica; Lorenzini, Patrizia; Cimini, Eleonora; Casetti, Rita; Tartaglia, Eleonora; Marchioni, Luisa; Petrosillo, Nicola; Palmieri, Fabrizio; D’Offizi, Gianpiero; Notari, Stefania; et al. (Cell death & disease, 2020)
The immunological mechanisms underlying the clinical presentation of SARS-CoV-2 infection and those influencing the disease outcome remain to be defined. Myeloid-derived suppressor cells (MDSC) have been described to be highly increased during COVID-19, however, their role remains elusive. We performed an in depth analysis of MDSC in 128 SARS-CoV-2 infected patients. Polymorphonuclear (PMN)-MDSC expanded during COVID-19, in particular in patients who required intensive care treatments, and correlated with IL-1β, IL-6, IL-8, and TNF-α plasma levels. PMN-MDSC inhibited T-cells IFN-γ production upon SARS-CoV-2 peptides stimulation, through TGF-β- and iNOS-mediated mechanisms, possibly contrasting virus elimination. Accordingly, a multivariate regression analysis found a strong association between PMN-MDSC percentage and fatal outcome of the disease. The PMN-MDSC frequency was higher in non-survivors than survivors at the admission time, followed by a decreasing trend. Interestingly, this trend was associated with IL-6 increase in non-survivors but not in survivors. In conclusion, this study indicates PMN-MDSC as a novel factor in the pathogenesis of SARS-CoV2 infection, and open up to new therapeutic options.